Sex differences in the scored Patient-Generated Subjective Global Assessment in 19,528 cancer patients - Wang, Yan-Li; Wu, Tian-Tian; Fu, Zhen-Ming; Guo, Zeng-Qing; Lin, Yuan; Shi, Ying-Ying; Hu, Wen; Ba, Yi; Li, Su-Yi; Li, Zeng-Ning; Wang, Kun-Hua; Wu, Jing; et al. (Journal of nutritional oncology, 2023)
Abstract Background The scored Patient-Generated Subjective Global Assessment (PG-SGA) has been widely used to assess the nutritional status of cancer patients. The purpose of this study is to compare the differences in PG-SGA scores and the 7 domain scores of the PG-SGA in male and female cancer patients. Methods This study was conducted at 72 hospitals from July 2013 to December 2018, a part of the Investigation on Nutritional Status and its Clinical Outcomes of Common Cancers. The PG-SGA was recorded to evaluate the nutritional status of patients. A total of 19,528 patients with 13 common malignancies were included in this study. Student t test and the χ2 test were applied to analyze the sex differences in the 7 domain scores. The Cancer Genome Atlas (TCGA) database was used to analyze the expression levels of symptom-related genes. Results There were significant sex differences in the PG-SGA (P = 0.032), notably in patients with gastric cancer (male vs female: 9.09 ± 4.86 vs 9.58 ± 5.07, P = 0.005) and esophageal cancer (9.64 ± 4.90 vs 10.46 ± 4.96, P = 0.011) and the average total PG-SGA of female patients was slightly higher than that of male patients (7.64 ± 4.98 vs 7.77 ± 5.14). The differences were mainly related to the weight, eating, symptom, as well as activity and physical function scores in the stratified analysis. Possible causes of the sex differences were the rates of nausea, vomiting, dry mouth, and other symptoms, in both gastric and esophageal cancer patients. Analysis of the TCGA database suggested that most of the related genes were sex neutral, except for genes related to dysphagia in gastric cancer (VEGFC was higher in female patients, VEGFA and VEGFB higher in male patients). Conclusions There are sex differences in the PG-SGA scores in patients with various tumor types (female patients generally had higher scores than male patients), with differences mainly in the weight, eating, symptom, as well as activity and physical function scores. The sex differences in PG-SGA scores might be due to the differences in the clinical manifestations of the disease, and further studies should be carried out to investigate other factors influencing the PG-SGA scores in cancer patients. This study provides basic data supporting the individualized nutritional treatment of cancer patients in clinical practice.